Laws and Emerging Technologies - Salmerón-Manzano, Esther (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Technologies will have a huge impact on society in the coming years and will bring new challenges and legal challenges to the legal sector worldwide. On the other hand, the new communications era also brings many new legal issues, such as those derived from e-commerce and payment services, intellectual property, or the problems derived from the use of new technologies by young people.